GYMNOPETALUM PECTINATUM (W. J. DE WILDE & DUYFJES) RUGAYAH: RANK OF SPECIES FOR GYMNOPETALUM SCABRUM VAR. PECTINATUM (CUCURBITACEAE) - -, W. J. J. O. DE WILDE & B. E. E. DUYFJES -; RUGAYAH, RUGAYAH (REINWARDTIA, 2015)
DE WILDE, W. J. J. O., DUYFJES, B. E. E. & RUGAYAH. 2015. Gymnopetalum pectinatum (W. J. De Wilde & Duyfjes) Rugayah: rank of species for Gymnopetalum scabrum var. pectinatum (Cucurbitaceae). Reinwardtia 14(2):323 - 324. - With Gymnopetalum pectinatum (W. J.de Wilde & Duyfjes) Rugayah, stat. nov.& comb. nov., a coastal species, four species in Gymnopetalum are now recognized in Malesia